Ecological challenges to ethics - Władysław Zuziak (Polonia Sacra)
This article is an attempt to shed new light on the environmental challenges of ethics related to over‑exploitation of the world by humanity. This article aims to formulate guidelines for the project of new ethics that will be able to respond to these challenges, to appreciate the intrinsic value of the world without diminishing the value of human being. The starting point of the analysis is the increase of ecological awareness, observable both among scientists and politicians as well as among citizens and the Church. In the next part of the article, contemporary ecological ethics are compared with traditional anthropocentric ethics. The paper presents the diagnosis of the reasons for the exploitation of nature resulting with ecological crisis and offers a method of overcoming the crisis. It argues in favour of anthropocentrism, but rejects its radical version. In the last part of the paper there is a proposal to create a new ethics, appropriate for us and the world, which would be an extension and refinement of Christian ethics in dialogue with contemporary secular trends.